King Lear - Shakespeare, William, 1564-1616 (Salt Lake City, UT : Project Gutenberg, 1998)
"King Lear" by William Shakespeare is a tragedy written in late 1605 or early 1606. Set in pre-Roman Britain, the play follows King Lear's catastrophic decision to divide his kingdom among his three daughters based on their declarations of love. When his youngest daughter speaks honestly rather than flatteringly, Lear disowns her, triggering a chain of betrayals, madness, and destruction. Known for its dark tone and themes of blindness and madness, the play is regarded as one of literature's greatest achievements. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/King_Lear
Release date is 1998-11-01
the PG Shakespeare Team, a team of about twenty Project Gutenberg volunteers
Keywords: Tragedies (Drama); Fathers and daughters -- Drama; Inheritance and succession -- Drama; Lear, King (Legendary character) -- Drama; Britons -- Drama; Kings and rulers -- Drama; Aging parents -- Drama